Na2SO4 addition on electro-dewatering of urban river sediment by horizontal circular electric field: Comparison of three different electrodes. Issue 15 (18th November 2019) - Wu, Pan; Li, Jianfeng; Pi, Kewu; Li, Qunqun; Guo, Xiaomei; Yuan, Jing; Wang, Zheng; Wang, Chen; Sun, Piao; Shi, Yafei; Liu, Defu; Gerson, Andrea R.
Abstract: The influence of Na2 SO4 addition on electro-dewatering of urban river sediment with iron, copper, or graphite anodes was investigated using the constant cell voltage of 30 V. The dewatering rate and energy consumption were affected by the concentration of Na2 SO4. The greatest dry solids content was achieved at Na2 SO4 dosage of 10  g   kg DS − 1 (DS – dry solids) with dry solids content for the iron, copper, and graphite electrodes of 56.8, 52.4, and 52.2 wt.%, respectively. With respect to an initial solid content of about 40 wt.%, the iron electrode performed the best with the dewatering rate of 3.62 g m −2 s −1 and energy consumption of 0.167  kWh  kg water − 1 . Due to the formation of a nonconductive coherent oxide film on the copper anodes, these performed the worst with dewatering rate of 2.31 g m −2 s −1 and energy consumption of 0.129  kWh  kg water − 1 . These outcomes help to provide the basis for the choice of electrodes and electrolyte dosage for electro-osmostic dewatering of river sediment.